2017
DOI: 10.1115/1.4036677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tip Gap Size on the Aerodynamic Performance of a Cavity-Winglet Tip in a Turbine Cascade

Abstract: The aerodynamic performance of a cavity-winglet tip is investigated in a high-pressure turbine cascade by experimental and numerical methods. The winglet tip has geometric features of a cavity and a suction side fore-part winglet. A cavity tip is studied as the baseline case. The aerodynamic performances of the two tips are investigated at three tip gaps of 0.8%, 1.7%, and 2.7% chord. At tip gaps of 1.7% and 2.7% chord, the loss near the blade tip is dominated by the tip leakage vortex (TLV) for both tips, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The profile of blade was redesigned from a typical highly-load high-pressure turbine blade. Many basic studies and experiments have been conducted on this kind of blade (Zhong and Zhou [17], Zhou and Zhou [18]).…”
Section: Methodsmentioning
confidence: 99%
“…The profile of blade was redesigned from a typical highly-load high-pressure turbine blade. Many basic studies and experiments have been conducted on this kind of blade (Zhong and Zhou [17], Zhou and Zhou [18]).…”
Section: Methodsmentioning
confidence: 99%
“…Among rotor tip designs: tip winglets, tip ribs and casing configuration are considered to be the best design to reduce tip thermal load. Zhong et al 17 constructed winglet cavity tip structure using numerical method and studied tip gap size effect. Yan et al 18 added winglets on both sides of tip and compared their effects on tip heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental measurement by Yaras and Sjolander 7 pointed out that the winglet tip design would reduce 10% of the tip leakage loss. Zhong et al 8 studied the aerodynamic performance of the suction-side winglet structure with different tip clearance sizes experimentally and numerically. The results showed that the suction-side rim structure effectively reduced the leakage flow intensity when the gap size was small.…”
Section: Introductionmentioning
confidence: 99%